2021
DOI: 10.3389/fpsyg.2021.749788
|View full text |Cite
|
Sign up to set email alerts
|

Examining Psychedelic-Induced Changes in Social Functioning and Connectedness in a Naturalistic Online Sample Using the Five-Factor Model of Personality

Abstract: The present study examines prospective changes in personality traits relevant to social functioning as well as perceived social connectedness in relation to the naturalistic use of psychedelic compounds in an online volunteer sample. The study also examined the degree to which demographic characteristics, social setting, baseline personality, and acute subjective factors (e.g., emotional breakthrough experiences) influenced trajectories of personality and perceived social connectedness. Participants recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 103 publications
(174 reference statements)
1
11
0
Order By: Relevance
“…Findings from the current and previous studies suggest that a psychedelic-assisted intervention can reduce levels of neuroticism, which are related to reductions in anxiety ratings in our study, and could be related to reductions of symptoms of comorbid conditions such as depression or post-traumatic stress disorder as seen in other studies. We also found post-retreat increases in trait agreeableness, which is in line with a previous naturalistic work done by Weiss et al ( 41 ). Other studies have shown either no changes in agreeableness post-psilocybin experience in depressed patients ( 37 ) or higher agreeableness scores among psychedelics users when compared to the general population ( 38 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Findings from the current and previous studies suggest that a psychedelic-assisted intervention can reduce levels of neuroticism, which are related to reductions in anxiety ratings in our study, and could be related to reductions of symptoms of comorbid conditions such as depression or post-traumatic stress disorder as seen in other studies. We also found post-retreat increases in trait agreeableness, which is in line with a previous naturalistic work done by Weiss et al ( 41 ). Other studies have shown either no changes in agreeableness post-psilocybin experience in depressed patients ( 37 ) or higher agreeableness scores among psychedelics users when compared to the general population ( 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…As such, it has been suggested that reducing neuroticism should be the primary focus of therapeutic interventions when treating psychopathologies such as anxiety (33). It has been repeatedly found that ingestion of a psychedelic drug can induce rapid and persisting changes in personality traits, and particularly reductions in neuroticism, in both healthy and clinical populations (24,(35)(36)(37)(38)(39)(40)(41). Thus, given the reduction in self-rated neuroticism found after ingestion of a psychedelic, it could be suggested that one mechanism by which psychedelic substances induce persisting changes in anxiety levels could be by altering maladaptive personality structures which exacerbate anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Not including adverse reactions driven more distinctly by external factors, such as harm due to accidents, abuse, or coercion by others, the most salient concerns regarding the intrinsic side effect profile of psychedelic drugs recently reviewed by Schlag et al (Schlag et al, 2022) refer to their potential to 1) trigger psychotic episodes (Smart et al, 1966;Metzner, 1969;Huang & Bai, 2011;Hodge et al, 2022), or more subtly, enhance schizotypal tendencies in healthy individuals (Lebedev et al, 2021;Weiss et al, 2021;Forstmann et al, 2020;Kettner et al, 2021), and 2) to induce enduring visuoperceptual aberrations, that, when distressing, are clinically recognised as hallucinogen persisting perception disorder (HPPD) (Halpern & Pope, 2003;Schlag et al, 2022;Cerón Tapia et al, 2021;Singh et al, n.d.;Nutting et al, 2021)). The latter has been identified in the literature as early as 1960 (COHEN, 1960) and is nowadays considered to include two sub-types.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of naturalistic studies found increases in self-reported connectedness related to the use of psychedelics ( Forstmann et al, 2020 ; Weiss et al, 2021 ; Petranker et al, 2022 ), and connectedness is canonically related to well-being, especially in the context of psychedelics ( Watts et al, 2017 ). The precise definition of connectedness and its relationship to meaning remains elusive, however, Forstmann et al (2020) examined the “Inclusion of Self in Others” ( Aron et al, 1991 ), in which participants select how much their sense of “self” overlaps with another.…”
Section: Meaning Connectedness and Salience In Psychedelicsmentioning
confidence: 99%